2011
DOI: 10.1007/s00268-011-1171-y
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Transcatheter Arterial Chemoembolization for Intrahepatic Cholangiocarcinoma after Curative Surgery: Retrospective Control Study

Abstract: Adjuvant TACE after radical surgery was associated with better survival among the ICC patients with early recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 61 publications
2
57
2
1
Order By: Relevance
“…There is still no wellestablished adjuvant therapy for patients with ICC after liver resection [4]. Preliminary results from previously reported studies suggested that adjuvant TACE might benefit selected patients, but these studies failed to clarify how to select these patients [11][12][13]. In our study, we tried to identify this subgroup of patients through survival risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still no wellestablished adjuvant therapy for patients with ICC after liver resection [4]. Preliminary results from previously reported studies suggested that adjuvant TACE might benefit selected patients, but these studies failed to clarify how to select these patients [11][12][13]. In our study, we tried to identify this subgroup of patients through survival risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed transarterial chemoembolization (TACE) to be beneficial for patients with advanced and unresectable ICCs [9,10]; however, to the best of our knowledge, only three studies reported the use of adjuvant TACE in ICC patients after curative resection. Shen et al reported that postoperative TACE failed to delay tumor recurrence but prolonged overall survival (OS) of patients with early tumor recurrence [11].Two other reports suggested that TACE improved survival of patients with ICC .5 cm or at an advanced TNM stage (stage III [T3N0M0] or IV [T4N0M0 and AnyTN1M0]) [12,13]. For patients with ICC at stage I (T1N0M0), this procedure not only failed to improve survival but might even promote tumor recurrence [13].These studies have been criticized because TACE was given to patients with varying degrees of predicted survival risk and because of relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable interest has been paid to various treatment options against ICC recurrence such as surgical treatment,6, 7, 8 chemotherapy,9 radiation therapy,7 radiofrequency ablation (RFA),10, 11 and transarterial chemotherapy 12, 13 with various degrees of success. In recent reports, aggressive surgical treatment for ICC recurrence led to good patient survival after recurrence, with a 3‐year overall survival (OS) rate of 25%,14 40%,6 and 100% 7.…”
Section: Introductionmentioning
confidence: 99%
“…The median OS in the adjuvant cTACE group was twelve months and surgery only resulted in a median OS of five months. However, cTACE did not delay the recurrence of the disease in this setting (14).…”
Section: A B Cmentioning
confidence: 64%
“…The most commonly used drug combination in the US and Europe consists of doxorubicin, cisplatin and mitomycin-C, but gemcitabine has also been used (13,14). The drug cocktail is brought into emulsion with Lipiodol, which has a dual function as a drug carrier as well as an embolic agent, that is able to penetrate the tumor vasculature up to the capillaries (12).…”
Section: Ctace-backgroundmentioning
confidence: 99%